PENGARUH BIAYA PROMOSI DARWIN AMBON YACHT RACE TERHADAP JUMLAH KUNJUNGAN WISATAWAN LUAR NEGERI DI KOTA AMBON - Alvian - Sapulette (Admisi dan Bisnis, 2016)
This final project review about the magnitudeof the influence of international eventspromotion Darwin Ambon Yacht Race againstthe level of foreign tourists visit in the town ofAmbon.The writing of this report are presented withstatistical Analysis using quantitative methodsand statistical diskriptifinferensial to obtainaccurate results influence the costs ofpromotion and promotion strategies that haverun Tourism Office of the SUcityof Darwin inAmbon Ambon Yacht Race. Method of datacollection using the field observation,interviews with officials of the Tourism Officeof the city of Ambon and stakeholders, as wellas reviews of Librarianship. Statisticalanalysis Statistical Analysis used isDescriptive in order to evaluate and explainthese forms of policy of promotion strategythat will run the statistics and analysis ofInferensial to know the relationship influencesthe cost of promotion by the number of visitsmatch the title of the research, namelyanalyzing the influence of Darwin-Ambonpromotion cost against the number of foreigntourists visit. The conclusions from the resultsof research through observation andinterviews conducted promotional policyisconducted by the Tourism office of the cityof Ambon not right on target due to the lackof number of foreign participants in thisannual event, this indicates that thepromotion has been running policy needs tobe reviewed in order to enhance the appeal ofanimo Darwin Ambon Yacht Race, includingalso in this case is the cost of the promotionsbecame major elements supporting thepromotion of these activities have influencesignificant in terms of channeling informationto improve the number of participants in thisinternational event. As for the second affectsthe number of foreign tourists to visit the cityof Ambon.